Feasibility of Gel Mask Peel Off Basil Leaves for Acne-Prone Facial Skin - Insy Mardiyan Tamami; Vivi Efrianova (Jurnal Tata Rias dan Kecantikan, 2022)
Basil leaf peel off gel mask as one of the basic ingredients of traditional cosmetics for acne-prone facial skin care. This study aims a) to determine the content of flavonoids, tannins and vitamin C contained in the basil leaf peel off gel mask b) find out the feasibility of the basil peel off gel mask in terms of texture, aroma, adhesion (organoleptic test) and panelist preferences (hedonic test). This research uses quantitative methods of pre-experiment method type. The place and time of the study was conducted at the FMIPA Laboratory and the Cosmetology and Beauty Laboratory of FPP UNP in January 2022. The object of study is basil leaves.The data sources used were 7 panelists, namely 1 beauty doctor, 1 chemical analyst, lecturer and 3 Cosmetology and Beauty students who had passed the cosmethodology course. The results of the analysis were obtained in kemngi leaves per 100gr of flavonoid content as much as 0.00104%, tannins as much as 0.0089% and vitamin C as much as 0.158%. Judging from the results of organoleptic tests on the texture aspect, the ratio of 10g: 2.5g got the highest score, namely 57.1% in the condensed category, in the aroma aspect the ratio of 15g: 2.5g got the highest score of 71.4% in the flavored category, at the closeness of the ratio of 10g: 2.5g got the highest score of 57.10% in the adhesive category and the panelists' favorability in the ratio of 10g: 2.5g got the highest score of 57.10% in the like category. The results of this study can be used as preliminary data for the next researchers in examining this problem regarding the basil leaf peel off gel mask to be further refined.